Катализ в азотной промышленности - Атрощенко В. И. Василий Иванович; Шапка А. В.; Веселов В. В.; Лобойко А. Я.; Власенко В. М. Василий Михайлович (Киев, Наукова думка, 1983)
Авт. указаны на обороте тит. л.